HUBUNGAN NUTRISI IBU, PERAWATAN PAYUDARA, KONTRASEPSI HORMONAL PADA IBU YANG MEMILIKI BAYI 1-6 BULAN DENGAN KELANCARAN PRODUKSI ASI - Irmiyati, Irma; Minata Wathan, Fika; Dewi Sartika Silaban, Titin; Rohaya (LPPM ISTeK ICsada Bojonegoro, 2023)
ABSTRACT Mother's Milk is the first natural food for the infants that provides all vitamins, minerals and nutrients. Complete nutrition in breast milk also contains immune substances such as IgA, IgM, IgG, IgE, lactoferrin, lysosomes, immunoglobulins that protect the infants from various diseases. Breast milk production that is not optimal comes to be a problem for mothers who have just given birth; as a consequence, many infants have less nutritional needs since mothers are not capable of providing the maximum breast milk based upon the nutritional needs of the infants. Breastfeeding that is not optimal can affect the occurrence of 45% of deaths due to neonatal infections, 30% of deaths due to diarrhea and 18% of deaths due to respiratory infections in infants. Factors determining the smooth production of breast milk include maternal nutrition, breast care and hormonal contraception. Thus, infants who do not get optimal breast milk will easily fall ill as their antibodies have not been fully and optimally formed. This study aims to determine the correlation of maternal nutrition, breast care and partial hormonal contraception among mothers who have infants aged 1-6 months with the smooth production of breast milk (ASI) at the Kertapati Health Center Palembang in 2021. This is a quantitative research using analytic survey method with cross sectional approach in which the research design used measurements or observations at the same time or one time. Sampling in this study used systematic random sampling (probability sampling). The data used in this study included primary data and secondary data. The data were analyzed by using the chi-square test and it obtained the p value = 0.022 > 0.05, indicating a correlation of maternal nutrition and the smooth production of breast milk. While the results of the Chi-square test for breast care on the smooth breast milk production obtained p value = 0.000 <0.05, which indicated a correlation of breast care and the smooth milk production. The results of the chi-square statistical test between hormonal contraceptives and the smooth production of breast milk showed p value = 0.00 <0.05, meaning that there was a significant correlation of hormonal contraception and the smooth production of breast milk at the Kertapati Health Center in Palembang. The midwives are expected to provide education and counseling to breastfeeding mothers so that breast milk production can be maximized and is expected to be a source of information for mothers who have the infants aged 1-6 months with smooth production of breast milk (ASI).